Respuesta :

Answer:

Step-by-step explanation:

-2/3x+9=4/3x-3=

x=6

Answer:

[tex]x=6[/tex]

Step-by-step explanation:

We have the equation:

[tex]-\frac{2}{3}x+9=\frac{4}{3}x-3[/tex]

First, we can remove the fractions by multiplying both sides by 3. Therefore:

[tex]3(-\frac{2}{3}x+9)=3(\frac{4}{3}x-3)[/tex]

Distribute:

[tex]-2x+27=4x-9[/tex]

Subtract 27 from both sides:

[tex]-2x=4x-36[/tex]

Subtract 4x from both sides:

[tex]-6x=-36[/tex]

Divide both sides by -6:

[tex]x=6[/tex]

Hence, the value of x is 6.